TNFα - A pivotal role in rheumatoid arthritis? - Brennan, F; Maini, R; Feldmann, M (1992)
This review seeks to describe data which support the concept that TNFα has a pivotal role in the pathogenesis of RA. There is now compelling evidence from in vitro studies and in animal models that this is the case. The in vivo studies suggest that the direct pathogenic effects of TNFα are amplified by its potential to act as a potent paracrine molecule by inducing other pro-inflammatory molecules such as IL-1, and GM-CSF. It has yet to be established whether similar paracine effects of TNF-α are observed in the collagen type II mouse, or in the human TNFα transgenic mice, where (as discused in this review), TNFα undoubtedly has a pathogenic involvement. During the ongoing inflammation in RA, TNFα (and other mediators?) induce the production of soluble TNF-R which can act a natural inhibitors. This process is, however, in adequate within the inflamed synovium, due to the fact that cytokine interactions are very local, through autocrine and paracrine mechanisms. In this environment there is a continuous competition between the interactions of surface or soluble receptor with TNFα. It may well be that soluble TNF-Rs play a more important role in the periphery where they act as an essential clearance mechanism for the ligand. If, as the available data suggest, TNFα does indeed have a pivotal role in the pathogenesis of RA, this needs to be verified by demonstrating that removal of TNFα locally in the synovial joint of RA patients has a significant effect on clinical paramaters of disease, and the progression of the disease process itself.